2019
DOI: 10.1016/j.bmcl.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Novel allosteric covalent inhibitors of bifunctional Cryptosporidium hominis TS-DHFR from parasitic protozoa identified by virtual screening

Abstract: Protozoans of the genus Cryptosporidium are the causative agent of the gastrointestinal disease, cryptosporidiosis, which can be fatal in immunocompromised individuals. Cryptosporidium hominis (C. hominis) bifunctional thymidylate synthase-dihydrofolate reductase (TS-DHFR) is an essential enzyme in the folate biosynthesis pathway and a molecular target for inhibitor design. Previous studies have demonstrated the importance of the ChTS-DHFR linker region "crossover helix" to the enzymatic activity and stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the context of antifolate resistance, development of new generation antifolates based on novel chemotypes is warranted. Although the fragment-based screening approach has been successfully applied to DHFR enzymes in various bacteria and protozoa 41,42 , no similar study has yet been reported in the malaria parasite Plasmodium falciparum. Here, we describe the first fragment-based screening on PfDHFR.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of antifolate resistance, development of new generation antifolates based on novel chemotypes is warranted. Although the fragment-based screening approach has been successfully applied to DHFR enzymes in various bacteria and protozoa 41,42 , no similar study has yet been reported in the malaria parasite Plasmodium falciparum. Here, we describe the first fragment-based screening on PfDHFR.…”
Section: Discussionmentioning
confidence: 99%
“…DHFR-TS In humans, the DHFR and TS enzymes exist as monomers, while in parasites, they exist as dimers on the TS-TS interface on the same polypeptide chain [ 22 ]. The protein–protein interface can serve as an essential target for small molecules.…”
Section: Structure and Sar Of The Selected Enzymesmentioning
confidence: 99%
“…It has been observed by the Ch DHFR-TS crystal structure that one DHFR domain of the dimer is linked to the other DHFR domain by the crossover helix making hydrophobic interactions. It moves back to the original monomer to complete the DHFR and TS domains [ 22 ]. From E. coli DHFR-folate-NADP + ternary complex, it was observed that the M20 loop adopts different confirmation as open-close or occluded according to the catalytic cycle, which is also the most flexible region of the DHFR [ 77 ].…”
Section: Structure and Sar Of The Selected Enzymesmentioning
confidence: 99%
See 2 more Smart Citations